2020
DOI: 10.3390/cancers12010153
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of the Metastatic Cascade by Physical Activity: A Narrative Review

Abstract: The purpose of this narrative review is to provide an overview of the currently available knowledge about the mechanisms by which physical activity may affect metastatic development. The search terms exercise [Title/Abstract] AND metastasis [Title/Abstract] returned 222 articles on PUBMED on the 10 February 2019. After careful analysis of the abstracts, a final selection of 24 articles was made. Physical activity regulates the levels of metastatic factors in each of the five steps of the process. Moderate inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
9
0
1
Order By: Relevance
“…Together this indicates that tumor progression could be slowed or prevented by physical activity and indeed physical activity regulates multiple steps of the metastatic cascade, as comprehensively reviewed in [247]. In summary, moderate intensity exercise appears to prevent tumor spread by normalizing angiogenesis, reducing circulating tumor cells and decreasing endothelial cell permeability [247][248][249]. On the contrary, high-intensity exercise may favor cancer dissemination and promote the formation of the premetastatic niche through excessive stress [247,250].…”
Section: Targeting Metastasis Via the Treatment Of Obesitymentioning
confidence: 98%
See 3 more Smart Citations
“…Together this indicates that tumor progression could be slowed or prevented by physical activity and indeed physical activity regulates multiple steps of the metastatic cascade, as comprehensively reviewed in [247]. In summary, moderate intensity exercise appears to prevent tumor spread by normalizing angiogenesis, reducing circulating tumor cells and decreasing endothelial cell permeability [247][248][249]. On the contrary, high-intensity exercise may favor cancer dissemination and promote the formation of the premetastatic niche through excessive stress [247,250].…”
Section: Targeting Metastasis Via the Treatment Of Obesitymentioning
confidence: 98%
“…In summary, moderate intensity exercise appears to prevent tumor spread by normalizing angiogenesis, reducing circulating tumor cells and decreasing endothelial cell permeability [247][248][249]. On the contrary, high-intensity exercise may favor cancer dissemination and promote the formation of the premetastatic niche through excessive stress [247,250]. In overweight or obese breast cancer survivors, moderate to vigorous exercise three times a week for 16 weeks reduced systemic levels of insulin, IGF-1 and leptin, and increased adiponectin [251].…”
Section: Targeting Metastasis Via the Treatment Of Obesitymentioning
confidence: 98%
See 2 more Smart Citations
“…On the contrary, many rodent models of exercise fail to show an effect on tumor growth and/or survival if the exercise regimen is first initiated after tumor inoculation [35][36][37][38]. To this end, MacNeil and colleagues [37] observed that exercise prior to tumor inoculation decreased metastasis as discussed above, whereas exercise after tumor inoculation did little on its own.…”
Section: Preclinical Data From Rodent Animal Models Of Cancer and Exercisementioning
confidence: 99%